Migrant workers in Thailand: Qualitative exploration of reporting workplace accidents and filing workers' compensation claims - Yotwilai, Nawiya (International Journal of Occupational Safety and Health, 2024)
Introduction: Reporting accidents in the workplace is a method to prevent accidents and injuries. Reporting could influence to safety improvement regarding the diminution of workplace injuries. They were completed reporting along with accuracy influence filing workers' compensation claims. Employers and migrant workers often ignore reporting workplace accidents. This exploration aims to demonstrate migrant workers' proceedings with crucial barriers to reporting workplace accidents and filing workers' compensation claims. Methods: The study conducted in-depth interviews involving the purposeful snowball sampling of 48 migrant construction workers who were employed legally and filed claims from 2019 to 2022 in Thailand. The interview process comprised semi-structured questions and probes with the flexibility to explore experiences for individual participants. The recorded information was transcribed into English. Transcripts were translated and coded in NVivo software. Results: Migrant workers often misunderstood and disbelieved the workers' compensation system before accidents occurred. Geographical distribution caused unequal opportunities for healthcare access. Mobility prohibition tended toward negative effects with the high rate of underreporting workplace injuries. Incomplete reporting contributed to the denial of filing claims with additional risks of liabilities. The trouble of filing claims related to difficult communication due to insufficient language skills. Migrant workers decided to have a reliance on traditional medicine. Conclusion: True reporting of workplace accidents can encourage employers to prevent future accidents. Migrant workers need to implement the regulations. The public agencies should provide an equal and effective system of workers' compensation.